UV disinfection audit of water resource recovery facilities identifies system and matrix limitations. (December 2022) - Rauch, Kyle D.; MacIsaac, Sean A.; Stoddart, Amina K.; Gagnon, Graham A.
Abstract: The use of ultraviolet (UV) light as a disinfectant in water resource recovery facilities is a well-accepted and increasingly popular disinfection option. Different assessment techniques, such as collimated beam testing, biodosimetry, fluorescent microspheres, and computational fluid dynamic modelling, exist to evaluate suitability and validate fluence of full-scale UV systems; however, each of these techniques has limitations. UV auditing overcomes these limitations by concurrently estimating the minimum fluence required to meet effluent discharge limits, providing direct inactivation results of the regulated organism, and estimating the minimum fluence achieved by an installed full-scale system. Four wastewater facilities with various treatment technologies and flowrates were selected to be audited. Bench-scale collimated beam performance fluence-response curves were developed for E. coli and the modeled data was compared to plant performance to determine system versus matrix limitations. The results found that UV auditing successfully identified system and matrix limitations for each of four different wastewater treatment facilities. Furthermore, seasonal differences between two sampling locations were confirmed via UV auditing. Seasonal water quality analysis of WWTF-C resulted in a more challenging wastewater matrix to treat with increasing influent E. coli during the Fall. The UV audit identified that WWTF-C was undersized and limited in its capacity. In summary, UV auditing provides a clear and robust method to better understand how wastewater treatment facilities perform and provides a novel approach to determine the fluence of an installed full-scale reactor. Graphical abstract: Unlabelled Image Highlights: Auditing approach determines fluence for operating full-scale UV reactor. Modeled E. coli fluence-response curves were capable in evaluating WWTFs performance. UV Audits revealed system/matrix limitations by coupling bench- and full-scale data. UV Auditing identified seasonal vulnerabilities of WWTFs studied.